Temporal Dynamics of Reproduction in Hemiramphus brasiliensis (Osteichthyes: Hemiramphidae) - Mônica Rocha de Oliveira; Sathyabama Chellappa (The Scientific World Journal)
The reproductive aspects of Hemiramphus brasiliensis were analyzed with a view to verify the temporal dynamics of reproduction. This paper presents data on sex ratio, length at first sexual maturity, macroscopic and histological aspects of gonad development, gonadosomatic index (GSI), reproductive period, and fecundity of H. brasiliensis. The fishes were captured from the coastal waters of Rio Grande do Norte, northeastern Brazil. Females of this species predominated in the sampled population and were larger in size than the males. The length at the first sexual maturation of males was 20.8 cm and that of females was 21.5 cm. The macroscopic characteristics of the gonads indicated four maturation stages. Histological studies of gonads of H. brasiliensis showed six phases of oocyte development and four phases of spermatocyte development. The batch fecundity of this species was 1153 (±258.22) mature oocytes for 50 g body weight of female. The microscopic characteristics of gonad development indicate that H. brasiliensis is a multiple spawner, presenting a prolonged reproductive period during the whole year, with a peak in the month of April, and is considered as an opportunistic strategist.